The relationship between self-reported sleep/awake bruxism and chronotype profiles of dental students - Bilir, Halenur; Yılmaz, Burcu (Cumhuriyet University Faculty of Dentistry, 2022)
Objectives: The aim of this study is to evaluate the possible relationship between the presence/absence of the self-reported sleep and/or awake bruxism and the chronotype profiles of dental students. Materials and Methods: The dental students of Istanbul Medipol University and Istanbul Medeniyet University participated in this study in the fall semester of the 2020-2021 academic year. Along with a form requiring students ‘demographic data, an 11-item questionnaire evaluating sleep quality and self-reported sleep and awake bruxism, and a 19-item Morningness-Eveningness Questionnaire (MEQ) determining the chronotypes were applied. The significance level was set at p? 0.05 for statistical analysis. Results: 171 students (female:128, 74.9%; male:43, 25.1%) participated in the study. The mean age was 22.3±2.2. There was no statistical difference between the presence or absence of the bruxism types and the chronotype profiles of the students. The sleep quality in the students with sleep bruxism was statistically lower than in other types of bruxism. The participants with sleep bruxism were statistically more likely to have difficulty concentrating on their daily activities than the participants with other types of bruxism.

Amaç: Bu çalışmanın amacı diş hekimliği fakültesinde eğitim gören öğrencilerin kendi bildirdikleri uyku ve/veya uyanıklık bruksizmi varlığı veya yokluğu ile kronotip profilleri arasındaki olası ilişkinin değerlendirilmesidir. Gereç ve Yöntemler: Bu çalışmaya 2020-2021 eğitim-öğretim dönemi güz yarıyılında İstanbul Medipol Üniversitesi ve İstanbul Medeniyet Üniversitesi’nde eğitim gören diş hekimliği öğrencileri katılmıştır. Demografik verilerle birlikte uyku durumlarını ve kendi bildirdikleri uyku ve uyanıklık bruksizmini değerlendiren 11 soruluk bir anket ile kronotip profillerini belirleyen 19 soruluk sabahçıl-akşamcıl anketi uygulanmıştır. İstatistiksel analiz için anlamlılık düzeyi P? 0.05 olarak ayarlanmıştır. Bulgular: Çalışmaya 171 öğrenci (kadın:128, %74,9; erkek:43, %25,1) katılmıştır. Yaş ortalamaları 22,3?2,2’dir. Öğrencilerin kendi bildirdikleri uyku ve/veya uyanıklık bruksizmi varlığı veya yokluğu ile kronotip profilleri arasında istatiksel olarak fark yoktur. Uyku bruksizmi olanlarda uyku kalitesi diğer bruksizm türlerine göre istatiksel olarak daha düşüktür. Uyku bruksizmi olanların günlük aktivitelere odaklanmada zorluk yaşamaları diğer bruksizm türlerine sahip olanlara göre istatiksel olarak daha yüksektir. Sonuçlar: Bruksizm varlığı veya yokluğu ile kronotip profilleri arasında bir ilişki yoktur. Ancak uyku bruksizmi hem uyku kalitesini hem de günlük aktivitelere odaklanmayı olumsuz yönde etkilemektedir.
Diş hekimliği öğrencilerinin kendi bildirdikleri uyku ve uyanıklık bruksizm varlığının kronotip profilleri ile ilişkisinin değerlendirilmesi
Keywords: Bruxism; Circadian Rhythm; Dentistry; Bruksizm; Sirkadiyen Ritim; Diş Hekimliği